El mite de Lucrècia contrafet: un text oblidat (1878). - ROCA RICART, RAFAEL (Scripta, 2023)
The long poem entitled Llucrècia profanada, which the Valencian writer Ramon Lladró Mallí described as a «semi-serious, semi-comical poem» and published in 1878, recreates in literature one of the myths of the classical tradition that has had the greatest impact on western civilization: the rape of the Roman noblewoman Lucrecia. However, the circumstance that makes it more unique is that its public presentation was linked to the foundation of Lo Rat Penat, the cultural society around which the Valencian branch of the Catalan Renaissance would gravitate. In this article we analyze the symbolism and meaning that, from the first moment, the work of Lladró acquired. And we venture the possible reasons why, despite being a title repeatedly evoked, it fell into oblivion.